S19: Making Sport Events and Physical Activity Promotion More Climate Friendly (Baltic Journal of Sport and Health Sciences, 2026)
This symposium brings together innovative research and practical strategies to advance sustainability across the spectrum of sport events and physical activity promotion. The presentations address themes ranging from eco-friendly event organisation, travel optimisation in recreational league play, attitudes of football fans regarding sustainability, to more general questions about how ready organisations in the sport sector are to work on sustainability goals.The first presentation introduces the “City, Green, Go!” toolkit, an initiative developed under a multi-partner Erasmus+ project. This toolkit empowers grassroots sports organisations, municipal authorities, and event organisers with actionable guidelines on reducing their carbon footprint. Focusing on seven core principles, including energy efficiency, biodiversity, catering, mobility, waste reduction, sustainable materials, and water conservation, the toolkit demonstrates how integrating environmental awareness into event planning can lead to more eco-friendly sport events.The second presentation investigates the environmental impact of travel in recreational league play. Employing algorithm-based optimisation, the study analysed travel distances from over 4,000 football matches in Germany. The findings reveal that strategically regrouping teams based on geographic proximity has substantial potential to reduce overall travel distances and CO₂ emissions.The third presentation focuses on embedding planetary health in the context of physical activity promotion. Drawing on survey data, this work explores the discrepancy between the high personal value placed on sustainability and its comparatively lower prioritisation within organisations. The insights highlight key barriers – political, financial, and cultural – that must be addressed to transform organisational practices and better integrate environmental priorities into sport event planning.The fourth presentation deals with the attitudes of football fans regarding perceived environmental corporate social responsibility. Survey results indicated that about 50% of the football fans used active transport options to get to the stadium. Also, many fans agreed that it was important to them that their club acted in an environmentally friendly way.Together, these contributions provide an overview of the opportunities and challenges to prepare the sport sector for a carbon neutral future.